KEMAMPUAN MORAL DAN AGAMA MELALUI IMPLEMENTASI NILAI-NILAI KEAGAMAAN DI SDK BEJO PENDIDIKAN GURU PENDIDIKAN ANAK USIA DINI STKIP CITRA BAKTI - Rosalia Lende; Marsianus Meka; Elisabet Tantiana Ngura; Efrida Ita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to improve the development of Moral and Religious Values ​​abilities in students at SDK Bejo through the implementation of religious values. Type of Research The method used in this research is descriptive qualitative. Data collection uses interview techniques, observation and data collection (documents). The documents collected function as supporting data. The validity of the data can be seen when conducting interviews and observations, namely by checking all activities carried out by educators and students in instilling Catholic religious values ​​in classroom learning. In this research, the teacher invites students to tell stories, play character building roles, get children used to praying before and after studying, praying before and after eating, this increases children's understanding of the religious teachings they adhere to and the religious values ​​they adhere to. provide an example to students and instill characters who are honest, caring, polite, respectful, by providing motivating stories to students, at SDK Bejo. The results of this research show that cooperation between teachers and parents is very important in developing the ability of Religious and Moral values ​​in students at SDK Bejo. The value of religion is to grow faith and love for God. These values ​​are very necessary to become the basis for early childhood in carrying out activities at the next age stage. In general, there is a positive impact that has a big influence on children's religious development, namely children become more diligent in reading the Holy Bible, praying more diligently and knowing God better.